2009
DOI: 10.1590/s0100-67622009000200012
|View full text |Cite
|
Sign up to set email alerts
|

Sistema de blocos prensados para produção de mudas de três espécies arbéreas nativas

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a viabilidade do uso de blocos prensados como recipientes na produção de mudas de Inga marginata, Jacaranda puberula e Zeyheria tuberculosa. O sistema de bloco prensado (440 cm³/muda) foi comparado com sacos plásticos (330 cm3 ) e tubetes de seção circular (280 cm 3 ). O substrato utilizado foi uma mistura de composto orgânico, moinha de carvão e solo argiloso (6:2:2). Após a prensagem, os blocos prensados apresentaram dimensões de 60 x 40 x 12 cm (comprimento, lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
2
7
0
9
Order By: Relevance
“…Some authors (SCHIAVO; MARTINS, 2003;FREITAS et al, 2006;KELLER et al, 2009) have reported a greater increase in height and/or diameter, in various different species of trees, when they were planted in pressed blocks. According to Daniel et al (1997) and Carneiro (1995), stem base diameter is the best measurement to use when evaluating the seedling's capacity to survive in the field.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some authors (SCHIAVO; MARTINS, 2003;FREITAS et al, 2006;KELLER et al, 2009) have reported a greater increase in height and/or diameter, in various different species of trees, when they were planted in pressed blocks. According to Daniel et al (1997) and Carneiro (1995), stem base diameter is the best measurement to use when evaluating the seedling's capacity to survive in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to Freitas et al (2005), seedlings planted in this kind of container can grow without their roots being confined, and with a morphological structure development closest to that found under natural conditions. These conditions lead to better root system development, with consequent greater absorption of water and nutrients, resulting in better development of the aerial part (LELES et al, 2000). Lisboa et al (2012) observed that the size of the container is a factor which affects the development of Australian cedar seedlings, highlighting the fact CARMO, E.R.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations